Belgium & Luxembourg - Elliott, Mark; Smith, Helena; Nevez, Catherine Le.; Louis, Regis St; Walker, Benedict (Carlton: Lonely Planet, 2022)
Lonely Planet$1 (Bs Belgium & Luxembourg is our most comprehensive guide that extensively covers all the countries have to offer, with recommendations for both popular and lesser-known experiences. Wander through Brussels$1 (BGrand Place, explore the caves of the Ardennes, and indulge in Belgian chocolate and beer; all with your trusted travel companion.s
Includes index.
Keywords: Belgium -- Guidebooks